Development of repaglinide microspheres using novel acetylatedstarches of bitter and Chinese yams as polymers (2016)
Tropical starches from Dioscorea dumetorum (bitter) and Dioscorea oppositifolia (Chinese) yams were acetylated with acetic anhydride in pyridine medium and utilized as polymers for the delivery of repaglinide in microsphere formulations in comparison to ethyl cellulose. Acetylated starches of bitter and Chinese yams with degrees of substitution of 2.56 and 2.70 respectively were obtained. Acetylation was confirmed by FTIR, 1 H NMR spectroscopy. A 32 factorial experimental design was performed using polymer type and drug-polymer ratio as independent variables. Particle size, swelling, entrapment and time for 50% drug release (t50) were dependent variables. Contour plots showed the relationship between the independent factors and the response variables. All variables except swelling increased with drug: polymer ratio. Entrapment efficiency was generally in the rank of Bitter yam > Ethyl cellulose > Chinese yam. Repaglinide microspheres had size 50 ± 4.00 to 350 ± 18.10μm, entrapment efficiency 75.30 ± 3.03 to 93.10 ± 2.75% and t50 3.20 ± 0.42 to 7.20 ± 0.55h. Bitter yam starch gave longer dissolution times than Chinese yam starch at all drug-polymer ratios. Drug release fitted Korsmeyer-Peppas and Hopfenberg models. Acety-lated bitter and Chinese yam starches were found suitable as polymers to prolong release of repaglinidein microsphere formulations.